2021
DOI: 10.3390/ma14113123
|View full text |Cite
|
Sign up to set email alerts
|

Damage Development on the Surface of Nickel Coating in the Initial Period of Erosion

Abstract: The common occurrence of the phenomenon of cavitation in many industries and the multitude of factors affecting the resistance to cavitation erosion of used materials contribute to the search for methods and appropriate parameters of coating application that are able to minimize the effects of erosion. To determine the validity of the developed application parameters and the method used, cavitation studies and microscopic observations of the development of erosion during the cavitation test were carried out. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…9a). Very short as well as the lack of incubation period was also noted by Li et al [53], who tested 316L steel, Wantang et al [54], who tested martensitic HNS steel and two CrNiMo stainless steel grades, Liu et al [55], who tested Cr-Mn-N steels, Szala [56], who tested the NiCrSiB hardfacings, and Zakrzewska et al [42], who also tested nickel coating but deposited by the different method (the electroless method). With increasing testing time to 60 min, the volume loss increased to 0.22, 0.06 and 0.15 mm 3 , respectively for the uncoated steel, Nickel 1 and Nickel 2 coating.…”
Section: Cavitation Erosion Testsmentioning
confidence: 70%
See 1 more Smart Citation
“…9a). Very short as well as the lack of incubation period was also noted by Li et al [53], who tested 316L steel, Wantang et al [54], who tested martensitic HNS steel and two CrNiMo stainless steel grades, Liu et al [55], who tested Cr-Mn-N steels, Szala [56], who tested the NiCrSiB hardfacings, and Zakrzewska et al [42], who also tested nickel coating but deposited by the different method (the electroless method). With increasing testing time to 60 min, the volume loss increased to 0.22, 0.06 and 0.15 mm 3 , respectively for the uncoated steel, Nickel 1 and Nickel 2 coating.…”
Section: Cavitation Erosion Testsmentioning
confidence: 70%
“…Nickel coatings can be deposited using different plating technologies, such as conventional electrodeposition [32,37], brush electroplating [38][39][40][41], as well as the electroless method [42].…”
Section: Introductionmentioning
confidence: 99%
“…The first method is to reduce the conditions for the formation of cavitation, and the second method is to specially treat the surface, including the application of anti-erosion coatings [3]. An analysis of the methods of forming coatings with the required characteristics showed that the use of magnetron or vacuum-arc discharge plasma is the most promising compared to thermodiffusion, detonation, and plasma methods [4,5]. The main principles of the use of vacuum-arc discharge plasma for coating deposition are described, in particular, in [6] by the staff of the National Science Center "Kharkov Institute of Physics and Technology".…”
Section: Introductionmentioning
confidence: 99%